Transient quasi-periodic oscillations at γ-rays in the TeV blazar PKS 1510-089. Issue 3 (21st December 2021) - Roy, Abhradeep; Sarkar, Arkadipta; Chatterjee, Anshu; Gupta, Alok C; Chitnis, Varsha; Wiita, P J
ABSTRACT: We present periodicity search analyses on the γ-ray light curve of the TeV blazar PKS 1510-089 observed by the Fermi Large Area Telescope. We report the detection of two transient quasi-periodic oscillations: A 3.6-d QPO during the outburst in 2009 that lasted five cycles (MJD 54906–54923); and a periodicity of 92 d spanning over 650 d from 2018 to 2020 (MJD 58200–58850), which lasted for seven cycles. We employed the Lomb–Scargle periodogram, Weighted Wavelet Z-transform, redfit, and the Monte Carlo light-curve simulation techniques to find any periodicity and the corresponding significance. The 3.6-d QPO was detected at a moderate significance of ∼3.5σ, while the detection significance of the 92-d QPO was ∼7.0σ. We explore a few physical models for such transient QPOs including a binary black hole system, precession of the jet, a non-axisymmetric instability rotating around the central black hole near the innermost stable circular orbit, the presence of quasi-equidistant magnetic islands inside the jet, and a geometric model involving a plasma blob moving helically inside a curved jet.